THE INFLUENCE OF THE EFFECTIVENESS OF INTERNAL CONTROL AND OBSERVANCE OF ACCOUNTING RULES ON ACCOUNTING FRAUD - Dewi Kusuma Wardani; Feny Nuraini (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This study aims to explain the influence of the effectiveness of internal control and observance of accounting rules on accounting fraud. The method used is quantitative. The data used is a data source by distributing the Google Form link to the Village Office in the Imogiri District via WhatsApp using a convenience sampling technique. Respondents who filled out as many as 111 respondents. The results of the study explain that the effectiveness of internal controls has no effect on accounting fraud, while compliance with accounting rules has an effect on accounting fraud. The higher the effectiveness of management control and compliance with accounting regulations, the lower the level of accounting fraud. Conversely, the weaker management's internal control and compliance with accounting rules, the greater the fraud that occurs.Keywords: Internal Control Effectiveness, Compliance With Accounting Rules, Accounting Fraud